275 Undergraduate Career Aspirations in Northern Ireland - a National Qualitative Study. (28th February 2022) - Madden, S.; Clements, J.M.; Martin, N.; Kirk, S.J.
Abstract: Introduction: Undergraduate career aspirations are accurately translated to chosen career paths. Understanding what influences these decisions has implications for future workforce planning. The aim of this study was to identify future career intentions in Northern Irish Medical Students. Method: An anonymous voluntary survey consisting of binominal, Likert and free text responses was distributed to all medical students registered at Queen's University Belfast (QUB). Data was collected over 6 weeks in April-May 2021. The primary outcome was future career aspiration and secondary outcome was the reported attrition rate from medicine. Local Ethical approval was obtained. Results: 202 responses were received (Response rate 15%). Two thirds (n = 135) were female. One third of respondents remained undecided about their future career choice, with senior students demonstrating greatest certainty in future career choice. Respondents were least likely to choose a career in Surgery (33%). Factors influencing these decisions were a lack of academic interest in the speciality, perceived workload, and the length of the training scheme. 10% of respondents were unsure or unlikely to pursue a career in Medicine after they graduated. Thematic analysis demonstrated, fear of making mistakes, poor work life balance and poor working environments as reasons for leaving medicine. Conclusions: Uncertainty over future career intention remains common with surgery the least popular speciality. The rate of potential attrition is concerning which warrants further investigation.